Information Technology Governance Between Iso 38500, Risk It and Val It in Private University - Zein, Afrizal; Farizy, Salman; Suharyanto, Eko; Tristianto, Chrisantus; Marwati, Fingki (Yayasan Gema Bina Nusantara, 2024)
This study explores the application of the ISO 38500, Risk IT, and Val IT frameworks in improving IT governance at the university. ISO 38500 provides general guidance for IT management by boards of directors, while Risk IT focuses on IT risk management and Val IT focuses on managing the value of IT investments. Qualitative research methods were used, including interviews with key stakeholders at Pamulang University. The research results show that the integration of the ISO 38500, Risk IT, and Val IT frameworks has helped universities optimize strategic decision-making regarding IT. Implementation of this framework increases transparency, accountability and holistic IT risk management across the university. However, challenges faced include a lack of deep understanding of the framework and the need to ensure consistency in implementation. Recommendations for the university include more intensive training for staff, strengthening communication between different units, and developing performance metrics that align with the university's strategic goals. This research makes an important contribution to the practical understanding of implementing effective IT governance in higher education environments, by highlighting the benefits and challenges of integrating the ISO 38500, Risk IT, and Val IT frameworks.